2012
DOI: 10.1002/etep.1696
|View full text |Cite
|
Sign up to set email alerts
|

Determination of economic dispatch of wind farm-battery energy storage system using Genetic Algorithm

Abstract: SUMMARY This paper considers the incorporation of battery energy storage systems (BESS) into wind farms, for the purpose of achieving economic dispatch for the wind power generators in a manner similar to conventional power plants. A BESS operation optimization model (BOOM) is introduced, and through utilizing unit commitment results, BOOM maximizes a predetermined objective that measures economic benefits obtained from the wind power dispatchability against the BESS cost. Due to the requirements of the formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Energy storage systems can help wind farms follow the regulated power and almost eliminate the influence of prediction errors . The basic principle to offset errors is to put ESS in a suitable condition with enough capacity to adjust its output.…”
Section: Auxiliary Assistance Of Ess In Wind Farmsmentioning
confidence: 99%
“…Energy storage systems can help wind farms follow the regulated power and almost eliminate the influence of prediction errors . The basic principle to offset errors is to put ESS in a suitable condition with enough capacity to adjust its output.…”
Section: Auxiliary Assistance Of Ess In Wind Farmsmentioning
confidence: 99%
“…From Figure D, it is observed that the number of input variables of GA is the summation of the number of elements of Q and R matrices. In GA process, all the input variables of the GA are encoded into one chromosome (bit stream) . This arrangement is composed of a set of twelve elements, where the first eight are corresponding to the Q matrix, and the remaining four are related to the R matrix.…”
Section: Control Strategies For a Dfigmentioning
confidence: 99%
“…The elementary steps of the GA that are used in this work to reach the best response to satisfy the minimum target function are as follows: The objective function of the system is represented by binary coding. Population size ( n p = 20), crossover probability ( P c = 0.8), and mutation probability ( P mu = 0.05) are chosen.…”
Section: Control Strategies For a Dfigmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the energy storage technology can play a prominent role in facilitating high penetration of wind energy [9]. Integrating the intermittent energy sources like wind energy with an energy storage system can achieve the economic dispatch for the power generator in a manner similar to conventional power plants [10]. Using an energy storage system would help the grid connection during the periods that grid is facing high peak demand and shifting the grid load from peak and busy time to a less demand time.…”
Section: Introductionmentioning
confidence: 99%